2013
DOI: 10.1002/bbb.1435
|View full text |Cite
|
Sign up to set email alerts
|

Latest trends in feedstocks for biodiesel production

Abstract: Edible seed oil biodiesel has been criticized due to its low sustainability and potential conflict with food and fiber production for the use of arable land, besides high water and fertilizer requirements. In this context, biodiesel from non‐edible sources, like animal fat, waste oil, insect oil, or single cell oil constitutes an alternative biofuel that omits the previous drawbacks. In this review and taking into account the previous consideration, the most interesting feedstocks for biodiesel production are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
76
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(79 citation statements)
references
References 169 publications
0
76
0
3
Order By: Relevance
“…Sahafi et al (2015) argued that based on their preliminary financial analysis, the economic feasibility and availability of SBE residual oil would make it a better option for biodiesel production than using the refined vegetable oil or WFO. Moreover, a number of studies reported significant improvements in the properties and performance of biodiesel-diesel fuel blends by dissolving waste polymers such as expanded polystyrene (EPS) in biodiesel produced from WFO and SBE oil (Mohammadi et al, 2012(Mohammadi et al, , 2013(Mohammadi et al, , 2014 Soapstock is a by-product from vegetable oil refinement (Pinzi et al, 2014). In 2009, the worldwide generation of soybean soapstock alone stood at 2.16 million tons, 6% of the soybean oil produced in the same year (Azocar et al, 2010).…”
Section: Waste-oriented Oil Feedstocksmentioning
confidence: 99%
See 2 more Smart Citations
“…Sahafi et al (2015) argued that based on their preliminary financial analysis, the economic feasibility and availability of SBE residual oil would make it a better option for biodiesel production than using the refined vegetable oil or WFO. Moreover, a number of studies reported significant improvements in the properties and performance of biodiesel-diesel fuel blends by dissolving waste polymers such as expanded polystyrene (EPS) in biodiesel produced from WFO and SBE oil (Mohammadi et al, 2012(Mohammadi et al, , 2013(Mohammadi et al, , 2014 Soapstock is a by-product from vegetable oil refinement (Pinzi et al, 2014). In 2009, the worldwide generation of soybean soapstock alone stood at 2.16 million tons, 6% of the soybean oil produced in the same year (Azocar et al, 2010).…”
Section: Waste-oriented Oil Feedstocksmentioning
confidence: 99%
“…This is ascribed to soapstock`s high water content of about 50% wt. which is also difficult to be removed because it is emulsified with lipids (Pinzi et al, 2014). Waste oil recovered from edible oil mills effluents through the application of novel technologies such as electrospun nanofibrous filters (Sundaramurthy et al, 2014) can also be considered as a low-cost, widely available, emerging, and interesting source for biodiesel production (Shirazi et al, 2014a).…”
Section: Waste-oriented Oil Feedstocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Biodiesel might be produced from different triglycerides sources such as vegetable oils (that can be edible, non-edible or waste oils), animal fats (mostly edible fats or waste fats) and microalgae oil [2]. The majority of biodiesel today is produced through homogeneous alkali-catalysed transesterification of edible vegetable oils using methanol.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is environment friendly, sustainable, biodegradable with higher flash point and equally usable in existing diesel based engines [30,31]. Its indigenous origin and renewability may provide opportunities for rural regions of the world as additional employments [32]. According to an estimate, the global production of ethanol and biodiesel during the year of 2010 was 35 and 87 billion liters respectively and now expected to rise over 58 and 161 billion liters by the year 2020.…”
Section: Introductionmentioning
confidence: 99%